Carotid Flow Time Compared with Invasive Monitoring as a Predictor of Volume Responsiveness in ICU patients - Tomislav Jelic; Jordan Chenkin (CINQUILL Medical Publishers Inc., 2023)
Objectives: Identifying patients who will have an increase in their cardiac output from volume administration is difficult to identify. We propose the use of carotid flow time, which is a non-invasive means to determine if a patient is volume responsive. Methods: Patients admitted to a critical care unit with a pulmonary artery catheter in place were enrolled. We perform a carotid flow time and pulmonary artery catheter measurement of cardiac output pre and post-passive leg raise and comparing the two. An increase of 10% change in the pre- vs. post-passive leg raise measurement would be indicative of a patient who is volume responsive. Results: We identified 8 patients who were volume responsive as determined by the gold standard pulmonary artery catheter. The sensitivity 87.5% and specificity 90.9%. Pearson correlation coefficient between PA-CO measurements and CFT was r=0.8316, indicative of strong correlation between the two measurements. Conclusion: In our patient sample of critically ill patients with pulmonary artery catheters, we found a strong correlation between corrected carotid flow times and cardiac output measurements from pulmonary artery catheters.